2012
DOI: 10.1371/journal.pntd.0001707
|View full text |Cite
|
Sign up to set email alerts
|

Geographical Distribution of Trypanosoma cruzi Genotypes in Venezuela

Abstract: Chagas disease is an endemic zoonosis native to the Americas and is caused by the kinetoplastid protozoan parasite Trypanosoma cruzi. The parasite is also highly genetically diverse, with six discrete typing units (DTUs) reported TcI – TcVI. These DTUs broadly correlate with several epidemiogical, ecological and pathological features of Chagas disease. In this manuscript we report the most comprehensive evaluation to date of the genetic diversity of T. cruzi in Venezuela. The dataset includes 778 samples colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
66
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 38 publications
4
66
0
5
Order By: Relevance
“…2010; Carrasco et al . 2012) and is ubiquitous among sylvatic transmission cycles across the parasite's endemic range (Llewellyn et al . 2009a).…”
Section: Introductionmentioning
confidence: 99%
“…2010; Carrasco et al . 2012) and is ubiquitous among sylvatic transmission cycles across the parasite's endemic range (Llewellyn et al . 2009a).…”
Section: Introductionmentioning
confidence: 99%
“…This successful parasite species is found from the southern United States to Argentinean Patagonia [3]. Trypanosomiasis due to T. cruzi is characterized as a complex zoonosis, transmitted by approximately 130 species of triatomines from the Reduviidae family (Hemiptera insects that are exclusively hematophagous at all life stages) and able to infect more than 150 species of wild and domestic mammals in 8 orders [4].…”
Section: Introductionmentioning
confidence: 99%
“…The aim was to obtain a deeper understanding of the molecular epidemiology of Chagas disease and the extent and implications of genetic exchange in T. cruzi. The international collaborators produced a large body of relevant published work, and an assessment of the wider geographical distributions and ecological associations of the six genetic lineages of T. cruzi 26,27,28,29,30,31,32,33,34 ( Figure 7). Most recently, this work has included the development of peptide-based T. cruzi lineage-specific serology for discovery of the reservoir hosts of TcII, TcV and TcVI 35,36 .…”
Section: Iec and Origins Of The Chagas Epinet And Leishepinetsa Networkmentioning
confidence: 99%
“…Most recently, this work has included the development of peptide-based T. cruzi lineage-specific serology for discovery of the reservoir hosts of TcII, TcV and TcVI 35,36 . This later research is beyond the scope of the current text but updates can be found in key recent reviews or by searches with appropriate keywords in PubMed [26][27][28][29][30][31][32][33][34] . Although the IEC was not directly involved in ChagasEpiNet, it was the research at the IEC, in conjunction with subsequent developments in molecular technologies that provided the platform for the productive ChagasEpiNet international initiative.…”
Section: Iec and Origins Of The Chagas Epinet And Leishepinetsa Networkmentioning
confidence: 99%